AKTIVITAS LUTUNG JAWA (Trachypithecus auratus) DI BLOK PANANDAAN, TAMAN NASIONAL GUNUNG CIREMAI - Sulaiman, Muhammad; Supartono, Toto; Nurdin, Nurdin (Jurnal Nusa Sylva, 2023)
Langurs (Trachypithecus auratus) is one of the protected primate species and knowledge about the daily activities of langurs is very necessary in preserving the population. This study aims to determine the activities of Javan langurs in the Panandaan Block, Gunung Cirermai National Park. The method used was scan sampling for moving, resting, social, eating and other activities, within predetermined time intervals. Data analysis was carried out quantitatively and descriptively to describe all types of daily activities of Javan langurs. Research has recorded as many as 23 individual langurs. Of the five activity categories observed, the activity with the highest proportion was locomotion with a percentage of 27.6% and the lowest activity was eating, namely 22%. The proportion that is not too far between the largest and smallest proportions indicates that the time spent on each activity is relatively even. The results of this research can help in preserving langur populations, especially groups that occupy locations bordering owned land.